Students' Empathy Attitude in Helping To Overcome Difficulties in Mobile Device Programming Learning - Bella, Setya; Basori, Basori; Kurniasari, Kurniasari (Universitas Sebelas Maret, 2023)
Learning is a process of making people or living creatures learn. Learning is very important for students in an era of increasingly rapid technology, one of which is learning to program mobile devices. Of course, in learning there must be achievements learning that must be achieved by students. To achieve learning, students must overcome challenges with different levels of difficulty. This level of difficulty can influence the emotional development of students, especially in providing a sense of empathy towards other students. This research raises the problem of the level of difficulty faced by students in the process of learning mobile device programming and how to empathize in helping students overcome these difficulties. This research method uses a qualitative method with a descriptive approach where the researcher describes the literature review and describes the answers to existing problems. By collecting data through interviews, observations and literature studies. This research was carried out at one of the 11th grade Surakarta State Vocational Schools in phase F on the achievements per mobile device programming element. Based on the results of research in learning mobile device programming, educators know the importance of understanding students' level of difficulty using theory Bloom's Taxonomy and students' empathetic attitude towards the difficulties they face based on Erik Erikson's theory. So that an empathetic attitude can influence students' success in achieving learning.